Enhancement of Mechanical Properties of Hybrid Composite Materials - et. al., Zaid Ghalib Abdul-kadhim Al-Jlaihawi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A hybrid composite materialsare one of the types to provide good suspension in wheeled vehicles application.By reducing weight of suspension systems, lowers total fuel exhaustion and costs.One of the most common approaches is to replace steel components with composite materials.To improve safety, comfort, and durability, composite have been introduced. Composite materials are corrosion resistant, have a good strength-to-weight ratio, and can store a lot of elastic strain. The aim of this study is to look into the structural properties of a hybrid compositematerials made of 95 percent Epoxy, 5% rubber, 5% glass fiber, and 5% hybrid composite of rubber and glass fiber. Since it has advantages over other approaches, hand layup was used in the fabrication. The mechanical experiments were used to determine the efficacy of the proposed composite leaf spring. We performed tensile, impact, hardness tests. When reinforcing fibers were used, the experimental results showed an improvement in hardness, impact, tensile strength. after the reinforcing fibers have been added, the best mechanical test results were obtained when hybrid reinforcement was used.